2018
DOI: 10.1007/s42161-018-0109-8
|View full text |Cite
|
Sign up to set email alerts
|

Is the presence of Trioza erytreae, vector of huanglongbing disease, endangering the Mediterranean citrus industry? Survey of its population density and geographical spread over the last years

Abstract: Is the presence of trioza erytreae, vector of huanglongbing disease, endangering the mediterranean citrus industry? survey of its population density and geographical spread over the last years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 2 publications
1
22
0
Order By: Relevance
“…Regarding the PRA models, the radial and radial random models did not represent the observed pattern of expansion of the area invaded by T. erytreae during the five years after its introduction in the Iberian Peninsula (see Figures S5 and S6 online). This finding agrees with the circumpeninsular distribution of the host, regardless of the local scattered distribution of citrus crops and trees in small orchards and gardens within the study area [30].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Regarding the PRA models, the radial and radial random models did not represent the observed pattern of expansion of the area invaded by T. erytreae during the five years after its introduction in the Iberian Peninsula (see Figures S5 and S6 online). This finding agrees with the circumpeninsular distribution of the host, regardless of the local scattered distribution of citrus crops and trees in small orchards and gardens within the study area [30].…”
Section: Discussionsupporting
confidence: 88%
“…After the first detection of T. erytreae in the Iberian Peninsula in 2014, a series of delimiting surveys were carried out to assess its distributional range [30]. It was found that the population had spread from Vilanova de Arousa (Galicia, Spain) to the north, following the coastal line of Galicia, and to the south following the Portuguese coastal line, reaching the Lisbon region [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, this species is commonly used as a rootstock for lemon and as a crop for the jam industry. All in all, it would be interesting to perform new feeding behavior assays with other citrus species, such as lemon, sweet orange or mandarin trees, since certain preference of T. erytreae have been seen in the fields where the most frequently grown citrus species are: lime, lemon, mandarins, sweet orange and grapefruit trees [60][61][62]. For our study, eight hours of EPG recording time was used as this is the standard time used in many previous similar EPG studies, e.g., in those involving B. trigonica, B. tremblayi and D. citri [45,54,63].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, under multiple choice conditions, which are actually like more real situations in the field, T. erytreae is unlikely to transmit the bacterium from one carrot plant to another because this species is not a host ( T. erytreae is not able to complete its life cycle on this species, although it can land or feed off of carrot plants). This fact could only occur sporadically; several reports have described rutaceous plants as the only hosts of T. erytreae [ 34 , 60 , 61 , 62 , 65 , 66 , 67 ]. In addition, previous studies using sampling methods at the level of the crop canopy have shown that the main psyllid species present in carrot fields is B. trigonica , followed by B. nigricornis in low proportions [ 27 , 29 ].…”
Section: Discussionmentioning
confidence: 99%